Forecast the behaviour of rock mass before taking up the excavation at deeper layers of the ore body Borska reka - Zlatanović Dragan; Milisavljević Vladimir; Ljubojev Milenko; Ignjatović Dragan (Mining and Metallurgy Engineering Bor, 2015)
This paper presents one possible approach for resolving some important issues related to the stability of underground rock structures at higher depths. The analysis is focused on forecast the behavior of rock mass before performing the mining excavation at deeper levels of the ore body 'Borska Reka'. Regardless of extensive previous research of the ore body 'Borska reka' and necessary parameters obtained for modeling of stress and strain that occur under the influence of mining excavation, additionally the estimation state of stress in the rock massif is also done. The stability analysis is shown for the roadway at the level XVII and forecast their stability for deeper level. As the result, it is expected that the level of uncertainty and risk associated with many identified geomechanical risks with management of rock massif will be reduced.